2010
DOI: 10.1101/gr.104471.109
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic clusters of transcription factor binding sites are a key component of human promoters and enhancers

Abstract: Clustering of multiple transcription factor binding sites (TFBSs) for the same transcription factor (TF) is a common feature of cis-regulatory modules in invertebrate animals, but the occurrence of such homotypic clusters of TFBSs (HCTs) in the human genome has remained largely unknown. To explore whether HCTs are also common in human and other vertebrates, we used known binding motifs for vertebrate TFs and a hidden Markov model–based approach to detect HCTs in the human, mouse, chicken, and fugu genomes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
208
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(224 citation statements)
references
References 76 publications
15
208
1
Order By: Relevance
“…Second, consistent with previous observations that functional enhancers often contain homotypic clusters of motif sites (62,63), the presence of additional PPARγ/RXR motif sites correlated strongly with enhancer activity. Candidate enhancers containing additional PPARγ/RXR motif sites showed nearly twofold higher enhancer activity than those with only a single motif site.…”
Section: Elements In the Sequence Flanking Pparγ Motifs Strongly Affectsupporting
confidence: 77%
“…Second, consistent with previous observations that functional enhancers often contain homotypic clusters of motif sites (62,63), the presence of additional PPARγ/RXR motif sites correlated strongly with enhancer activity. Candidate enhancers containing additional PPARγ/RXR motif sites showed nearly twofold higher enhancer activity than those with only a single motif site.…”
Section: Elements In the Sequence Flanking Pparγ Motifs Strongly Affectsupporting
confidence: 77%
“…This modular organisation of the over-represented motifs in SGs supports their regulatory potential, as transcription factors are well known to interact with other cofactors, likely aided by colocalisation into compact CRMs (Howard and Davidson, 2004;Wasserman and Sandelin, 2004). Moreover, the multiple occurrence of a de novo identified motif within the same CRM is in agreement with previous studies that have shown that local clustering of transcription factor binding sites is a feature of vertebrate enhancers (Gotea et al, 2010).…”
Section: Research Articlesupporting
confidence: 78%
“…Phylogenetic conservation has been used as an indicator for functional conservation of enhancers throughout evolution (16,(27)(28)(29)(30)(31)(32); however, varying degrees of sequence conservation between cell types in different species have been observed. In some human tissues, such as forebrain, enhancers are subject to stringent evolutionary constraint, whereas in others, such as heart, they are under weak evolutionary constraint (12,16,(33)(34)(35)(36)(37)(38). In some cell and tissue types, structural and functional conservation of enhancer elements is significantly lacking, even between species as close as mice and humans (34).…”
mentioning
confidence: 99%